Association of Japanese cedar pollen sensitization in children with Dermatophagoides pteronyssinus sensitization and maternal sensitization: Insights from the Yamanashi adjunct study within the Japan Environment and Children’s Study (JECS) - Ayumi Shimamura; Ryoji Shinohara; Megumi Kushima; Sanae Otawa; Hideki Yui; Tomokazu Matsuoka; Daisuke Watanabe; Hiroshi Yokomichi; Kunio Miyake; Reiji Kojima; Zentaro Yamagata; Daiju Sakurai (Allergology International)
Background: In recent years, the prevalence of allergic rhinitis (AR) in Japanese children has increased significantly. Multiple sensitization and genetic factors are associated with the development of AR, and moreover, multiply sensitized children are more likely to have parents with AR. This research investigated the association of Japanese cedar pollen (JCP) sensitization in children with Dermatophagoides pteronyssinus (DP) sensitization and with maternal JCP sensitization. Methods: This is an Adjunct Study to the Japan Environment and Children’s Study (JECS) in Yamanashi where reports the highest positive rate of JCP sensitization. It included 1469 mother-child pairs who participated in a comprehensive health examination of 8-year-old children (from 2019 to 2022) at the JECS-Yamanashi. Univariate and multivariate logistic regression models were created using the presence/absence of child’s JCP sensitization as the objective variable; mother’s JCP sensitization and child’s DP sensitization as explanatory variables; and child’s sex and BMI, mother’s age, and JCP exposure in the examination year as adjustment variables. Results: Children who were positive for DP sensitization were also more likely to be positive for JCP sensitization (adjusted OR: 6.58; 95%CI: 5.10–8.48; P < 0.001). Children who were positive for DP sensitization were also more likely to be positive for JCP sensitization if their mothers were positive for JCP sensitization (adjusted OR: 1.77; 95%CI: 1.16–2.71; P = 0.008). Conclusions: JCP sensitization is associated with DP sensitization in children. Furthermore, in DP sensitization-positive children, JCP sensitization of the child was associated with JCP sensitization of the mother.